Secondary Development and Application of Satellite Dynamic Simulation Platform Based on ABAQUS - Zhang, Xiaotong; Ma, Wenlai; Jiao, Xiaolei (IOP conference series. Materials Science and Engineering, 2018)
As a strong coupling system, structure of the whole satellite has too many design parameters which are undetermined before initial design. In order to overcome the existing problems such as high update frequency of related parameters, complexity of the mouse operation and the low effectiveness of manual modelling, based on secondary development of ABAQUS, a satellite dynamic simulation platform is carried out. First of all, a convenient and friendly user interface is established by writing registration file and the dialog interface creation file based on Python scripting language. Besides, kernel execution scripts is also developed based on Python scripting language, therefore, the parametric and automation modelling as well as simulating process are realized and the efficiency of analysis can be improved.